THE POST-COMMUNIST NOVEL OF TRANSITION AS REALISM OF TRANSITION. THEMATIC PRECEDENTS IN ROMANIAN AND EAST-CENTRAL EUROPEAN LITERATURE - CONTEA, Bogdan; PIETRARU, Iulia (Studia Universitatis Babeș-Bolyai Philologia, 2024)
The Post-Communist Novel of Transition as Realism of Transition. Thematic Precedents in Romanian and East-Central European Literature. The present study aims to analyze how certain narrative formulas circulate within the world literary system – one but unequal (Moretti 2004, WReC 2015) – starting from the case of the novel of post-communist transition, specific to many Eastern European literatures. The Romanian literature abounds in such novels, which take various forms according to the different literary paradigms from which they have emerged. Thus, we consider that post-communist Romanian literature, or at least its social-political regime of relevance, is a symptomatic case of what the authors of Combined and uneven development: Towards a new theory of world-literature (WReC) call “(semi-)peripheral irrealism”. According to this study, the literature produced in peripheries and semi-peripheries is often formally dominated by a series of practices identified as specific to modernism, which arise, determined by the condition of the semi-periphery, in the unique and uneven system of world-literature, in which fiction becomes the narration that mediates lived experience in the “palimpsestic, combinatory and contradictory ‘order’ of peripheral experience.” (WReC). Nevertheless, a new direction of contemporary prose is being traced recently in order to rethink/ reproblematize the past and the way it can be reflected in literature. A series of recent novels such as Bogdan Coșa’s How Close the Cold Rains Are (2020) and Mihai Duțescu’s Beech Sponges (2021), as well as others, give rise to a new aesthetic formula of the post-communist novel of transition through the ways in which they operate with realism. We therefore propose to investigate the recent history of the phenomenon of fictional representation of the Romanian transition in relation to similar phenomena in East-Central Europe, while also analyzing the specifics of “the realism of transition” (as we will call this new literary category, in the footsteps of Mihnea Bâlici). Romanul tranziției post-comuniste românești ca realism al tranziției. Precedente tematice în literatura română și est-central europeană. Lucrarea de față își propune să analizeze modul în care anumite forme narative circulă în interiorul sistemului mondial literar – unul dar inegal (Moretti 2004, WReC 2015) – plecând de la cazul romanului tranziției postcomuniste, specific pentru multe dintre literaturile Europei de Est. Literatura română abundă de astfel de romane, acestea luând diverse forme, conform diferitelor paradigme literare din care au luat naștere. Noi argumentăm însă că literatura română postcomunistă, sau cel puțin regimul ei social-politic de relevanță, reprezintă un caz simptomatic pentru ceea ce autorii studiului Combined and uneven development: Towards a new theory of world-literature (WReC) numesc “irealism (semi-)periferic”. Conform studiului, literatura produsă în periferii și semiperiferii e adesea dominată formal de o serie de practici identificate drept specifice modernismului, ce iau naștere, determinate fiind de condiția semiperiferiei în sistemul unic și inegal al world literature, în care ficțiunea devine relatarea ce mediază experiența trăită în “«ordinea» palimpsestică, combinatorie și contradictorie a experienței periferice” (WReC). Cu toate acestea, în ultimii ani se trasează o nouă direcție a prozei române contemporane în vederea regândirii/ reproblematizării trecutului și a modului în care acesta poate fi reflectat literar. O serie de romane recente precum Cât de aproape sunt ploile reci (2020) de Bogdan Coșa sau Bureți de fag (2021) de Mihai Duțescu, dar și altele, dau naștere unei noi formule estetice a romanului tranziției postcomuniste prin modurile în care operează cu realismul. Ne propunem așadar să investigăm istoria recentă a fenomenului reprezentării ficționale a tranziției românești în relație cu fenomene similare din literaturile est-central europene, analizând totodată specificul “realismului tranziției” (așa cum vom numi această nouă categorie literară, pe urmele lui Mihnea Bâlici). Cuvinte-cheie: roman al tranziției, literatură (semi-)periferică, realism periferic, postcomunism, realismul tranziției Article history: Received 02 February 2024; Revised 21 April 2024; Accepted 25 April 2024; Available online 25 June 2024; Available print 30 June 2024.